2016
DOI: 10.1097/pgp.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

Primary Endometrial Yolk Sac Tumor With Endodermal-Intestinal Differentiation Masquerading as Metastatic Colorectal Adenocarcinoma

Abstract: Yolk sac tumors (YSTs) with a somatic glandular pattern can be difficult to recognize histologically because they reproduce developing intestinal, hepatic, or lung tissue and can express markers such as CDX2 and TTF1. We report an unusual case of a primary endometrial YST showing florid endodermal-intestinal differentiation in a 63-yr-old woman with a history of colorectal adenocarcinoma. Histologically, the tumor exhibited a glandular and papillary architecture and showed widespread immunoreactivity for CDX2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…A review of the literature identified 11 previously reported cases of primary endometrial YSTs, four of which were associated with a somatic epithelial neoplasm. 44 In two of our cases, the YST component was a purely hepatoid variant; one of these was a pure YST and the other was admixed with a HGSC. These cases were reported originally as a pure ovarian hepatoid carcinoma and a combined HGSC and hepatoid carcinoma.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…A review of the literature identified 11 previously reported cases of primary endometrial YSTs, four of which were associated with a somatic epithelial neoplasm. 44 In two of our cases, the YST component was a purely hepatoid variant; one of these was a pure YST and the other was admixed with a HGSC. These cases were reported originally as a pure ovarian hepatoid carcinoma and a combined HGSC and hepatoid carcinoma.…”
Section: Discussionmentioning
confidence: 58%
“…[35][36][37][38][39][40][41][42][43] These are thought to have a similar histogenesis to the corresponding ovarian neoplasms. We recently reported one such case (case 18 in this series 44 ). This occurred in a 63-yearold woman with a history of colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Regarding the age of our patient, the possibility of yolk sac tumour seems to be implausible [20]. Nevertheless, some authors argue for the existence of yolk sac tumour of the endometrium in postmenopausal patients based on AFP expression [17, 21]. However, it has been shown that gastric and colorectal cancers can express AFP as well, which can be used as serological biomarker [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…We have identified only a few published reports of endometrial YSTs in PubMed, affecting patients aged 17 to 65 years. [ 1 2 ] Among the cases, the most frequent symptom was abnormal vaginal bleeding, but presurgical endometrial biopsy allowed correct diagnosis of YST in only five cases. YSTs can show variable presentation under a microscope, and pathologists may have difficulty in differentiating microcystic or endodermal sinus-like structures from clear-cell carcinoma.…”
mentioning
confidence: 99%